Synthesis and Coordination Behavior of a New Hybrid Bidentate Ligand with Phosphine and Silylene Donors. Issue 5 (14th December 2020) - Nazish, Mohd; Siddiqui, Mujahuddin M.; Kumar Sarkar, Samir; Münch, Annika; Legendre, Christina M.; Herbst‐Irmer, Regine; Stalke, Dietmar; Roesky, Herbert W.
Abstract: This work describes the synthesis and coordination behavior of a new mixed‐donor ligand PhC(N t Bu)2 SiC6 H4 PPh2 (1 ) containing both silylene and phosphine donor sites. Ligand 1 was synthesized from a reaction of ortho ‐lithiated diphenylphosphinobenzene (LiC6 H4 PPh2 ) with chlorosilylene (PhC(N t Bu)2 SiCl). Treatment of 1 with Se and GeCl2 resulted in Si IV compounds 2 and 3 by selective oxidation of the silylene donor. This strong σ‐donor ligand induces dissociation of CuCl and PhBCl2 leading to formation of ionic complexes 4 and 5 respectively. The reaction of 1 with ZnCl2 and AlCl3 resulted in the formation of chelate complexes 5 and 7, respectively, while treatment with EtAlCl2 and GaCl3 forms monodentate complexes 8 and 9 . X‐ray analysis of 4 showed that the copper is in the spiro center of the two five‐membered rings. Moreover, the copper(I)chloride has not been oxidized but dissociates to Cu + and [CuCl2 ] − . All the compounds are well characterized by mass spectrometry, elemental analysis, NMR spectroscopy, and single‐crystal X‐ray diffraction studies. Abstract : A ligand with different Lewis base donor sites of phosphorus(III) and silicon(II). The ligands are arranged in 1, 2‐position at the benzene ring to generate mainly five‐membered ring compounds containing a metal atom. The exceptions of the compounds show clearly that the metal is preferentially coordinated to the silylene atom rather than to the phosphane site of the ligand.